Melting of Refractory Mantle at 1·5, 2 and 2·5 GPa under Anhydrous and H2 O-undersaturated Conditions: Implications for the Petrogenesis of High-Ca Boninites and the Influence of Subduction Components on Mantle Melting - Falloon T.J.; Danyushevsky L.V. (My University, 2000)
Boninites are an important ‘end-member’ supra-subduction zone magmatic suite as they have the highest H2O contents and require the most refractory of mantle wedge sources. The pressure–temperature conditions of boninite origins in the mantle wedge are important to understanding subduction zone initiation and subsequent evolution. Reaction experiments at 1·5 GPa (1350–1530°C), 2 GPa (1400–1600°C) and 2·5 GPa (1450–1530°C) between a model primary high-Ca boninite magma composition and a refractory harzburgite under anhydrous and H2O-undersaturated conditions (2–3 wt % H2O in the melt) have been completed. The boninite composition was modelled on melt inclusions occurring in the most magnesian olivine phenocrysts in high-Ca boninites from the Northern Tongan forearc and the Upper Pillow Lavas of the Troodos ophiolite. Direct melting experiments on a model refractory lherzolite and a harzburgite composition at 1·5 GPa under anhydrous conditions (1400–1600°C) have also been completed. Experiments establish a P, T ‘melting grid’ for refractory harzburgite at 1·5, 2 and 2·5 GPa and in the presence of 2–3 wt % H2O. The effect of 2–3 wt % dissolved H2O produces a liquidus depression in primary boninite of ?112 ± 19°C at a given temperature. The H2O-bearing melts, recalculated to 100 wt % anhydrous, are ?2–6 wt % higher in MgO, ?1–2 wt % higher in SiO2 and ?1–1·5 wt % lower in FeO, compared with nominally anhydrous melts at the same P and T. These differences are consistent with a change in the melting reaction, resulting in a higher contribution of orthopyroxene to the melt phase, compared with anhydrous conditions. We conclude that high-Ca boninite petrogenesis requires temperatures as high as ?1480°C at depths of ?45 km in the mantle wedge; these are constraints for any proposed model of intra-oceanic subduction zones. A comparison of the results from the boninite–harzburgite reaction experiments with the direct melting experiments on refractory lherzolite and harzburgite indicates that the influence of subduction components (included in the composition of the added model boninite) is to cause high-pressure melting cotectics to move towards the olivine apex (i.e. to relatively higher pressures) of the molecular normative projection from diopside onto the base of the ‘basalt tetrahedron’ [Jd + CaTs + Lc–Qz–Ol] compared with anhydrous melting of normal mantle in the absence of a subduction component. The subduction component involved in high-Ca boninite petrogenesis in addition to H2O has relatively high Al2O3 and Na2O contents. The experimental data from this and other studies empirically quantify the absolute effect of dissolved H2O (0·2–21 wt %) on the liquidus depression of olivine-saturated basaltic melts with ?<3 wt % total alkalis as follows: olivine liquidus depression (°C) = 74.403 ? (H2O wt %)0·352. The equation that describes this empirical relationship is non-linear with an error of ?9 relative percent.